Everything on DDoS Attacks, DDoS incidents & DDoS Defense Mechanisms! - Naveen Sharma, Dr. Keshav Dev Gupta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Distributed denial-of-service (DDoS) is a rapidly growing problem. DDoS attacks have suddenly gained popularity in the last 10 years. Furthermore, their intensity to attack has increased and now ranges from just a normal problem to a severe illegal cyber activity. The increasing number of malicious attacks cause a great loss of revenue who become the targets of this. For the protection of these attacks from happening, there is a sudden rise in the market for DDoS Protection Service (DPS) providers from whom the victims can easily ask for help by using their traffic diversion systems and DDoS protection measures. The multitude and variety of attacks and the defense system approaches are flooding. This article presents various classifications of attacks and defense mechanisms. The attack classification criteria done in this article describe the commonalities among them. Furthermore, features of attack strategies, the challenges in protecting them, and ideating a new easy-to-go hassle-free system for DDoS attack protection is another daunting task. In this research article, based on PH.D.topic "An Approach to Protect DDoS Attack" briefly describes the happening of different DDoS attacks, their mechanism of attack, types of different DDoS attacks, and some important methods being used in protecting DDoS attacks from happening. After finding out the limitations/drawbacks and disadvantages in the current DDoS protection measures, we will detail you with the Hybrid Approach effective and efficient in protecting and mitigating DDoS attacks without eliminating IPs and continuing the flow of legitimate traffic at servers online.